The Relationship between Personality and Career Decision Making Self Efficacy Among Pra-University Student at Machang, Kelantan. - Zulkifli, Firzanah Al Zahra; Ab. Rahman, Othman; Musa, Nurun Najihah (‘Abqari Journal, 2021)
This study was conducted to explore the differences in personality and level of career decision-making self-efficacy (CDMSE) by gender among pre-university students. Besides, this study also conducted to identify the relationship between personality and CDMSE among pre-university students. This study uses a mixed method design in determining the relationship between personality and self-efficacy in career decision making. The respondent be selected by using simple random sampling method, as 175 student Pre-University and 5 respondents were selected to interview in obtaining qualitative findings. Data was collected by using Big Five Inventory-2 (BFI-2) and Career Decision Making Self-efficacy Scale Short Form (CDMSE-SF). Data analyzed using Statistical Package Social Science 25.0 (SPSS). The results showed no difference between conscientiousness (t(173)=0.280,p<0.05), openness (t(173)=0.613,p<0.05), neuroticism (t(173)=1.434,p<0.05), agreeableness (t(173)=0.857, p<0.05, extraversion (t(173)=-0.559, p<0.05) and level of CDMSE (t(173)=1.558, p<0.05). The finding also revealed that conscientiousness, (r=0.505**, n=175, p<0.05) openness, (r=0.212**, n=175, p<0.05) neuroticism, (r=0.366**, n = 175, p<0.05) and extraversion (r=0.486**, n=175, p<0.05) had a significant relationship with CDMSE among Pre-University students. However, there is no significant relationship between agreeableness and CDMSE (r=0.128, n=175, p<0.05). The result was supported by qualitative findings, which show the relationship between personality and CDMSE. This study is significant for students, counselor, and educators in helping students related to their careers.